STUDI EVALUASI PROGRAM GARDA AMPUH PENDIDIKAN KESETARAAN PAKET A,B,C DI KABUPATEN BANYUWANGI - Zaki Al Mubarok (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2017)
This study is an evaluation study of the Garda Ampuh Program equal education package A, B, C in Banyuwangi. This program is a non-formal education program imposed by the Government of Banyuwangi in an attempt to run education services to people who have children out of school because of limited funds. This research is a qualitative descriptive field. Outline the implementation of the program of educational equality Powerful Guard Package A, Package B, and Package C runs properly, effectively and efficiently. This is evidenced by the large number of students who join the program are powerful Guard education equality Package A, Package B, and c. it is also supported by data Guard program Powerful learners education equality Package A, Package B, and C the national education examination equality (UNPK).